Effects of Soaking Time and Temperature on the Nutritional Content and Sensory Quality of Soybean Flour and Milkffects of Soaking Time and Temperature on the Nutritional Content and Sensory Quality of Soybean Flour and Milk (Global Journal of Science Frontier Research, 2019)
Soybean plays a great role to reducing protein-energy malnutrition. However, the major problems in raw soybeans are off-flavor. Processing also affect nutritional value unless optimum processing methods were used. Thus, this investigation was carried out to evaluate the effect of soaking temperature and time on proximate composition and sensory properties of soy products made from soybean variety AFGAT (Glycine max). Two soaking temperatures hot water (40°C) and ambient temperature (25°C) and three soaking times (8, 12 and 16 hrs) were considered in the experiment. The study revealed that soaking time and the temperature had significantly (p
Keywords: soaking time and temperature; proximate composition; soybean; soybean flour; soy milk